2017
DOI: 10.1002/phar.2025
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis for Massive Pulmonary Embolism in Pregnancy

Abstract: Pregnant women are at high risk for venous thromboembolism, including pulmonary embolism (PE), given expected changes in coagulation, fibrinolysis, and venous blood flow. In fact, PE is the leading cause of maternal death in the United States. Nonpregnant patients who develop PE with hypotension or show signs of deterioration after anticoagulation receive thrombolytics as a standard of care. Pregnant women, however, have been excluded from clinical trials with thrombolytics, and all data available in this popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 58 publications
(130 reference statements)
0
10
0
3
Order By: Relevance
“…In a literature review, 23 cases involving the use of systemic thrombolysis in pregnancy for massive PE were identified. 45 There were no maternal deaths, and bleeding complications were reported in 39% of the cases. Bleeding was classified as major in 22% of women, 9% of the fetuses died, and 39% of pregnancies resulted in preterm delivery.…”
Section: -3 Items Presentmentioning
confidence: 86%
“…In a literature review, 23 cases involving the use of systemic thrombolysis in pregnancy for massive PE were identified. 45 There were no maternal deaths, and bleeding complications were reported in 39% of the cases. Bleeding was classified as major in 22% of women, 9% of the fetuses died, and 39% of pregnancies resulted in preterm delivery.…”
Section: -3 Items Presentmentioning
confidence: 86%
“…There is currently no consensus surrounding the use of systemic or catheter direct thrombolysis as a primary treatment for patients who present with a submassive PE, due to controversy regarding risk-benefit ratio. Compared to systemic thrombolysis, CDT has the potential to lower the risk of bleeding by localizing drug delivery directly to the area of interest, allowing for a two-thirds reduction in the required dose ( 7 ). Numerous studies have demonstrated the efficacy and safety of CDT for PE in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The primary concern for this patient was that without thrombolysis, cardiac dysfunction would worsen with ongoing pregnancy, with the potential for catastrophic urgent preterm delivery or decompensation during term delivery. CDT was chosen over systemic thrombolysis to minimize the dose of tissue plasminogen activator, given concerns regarding risk of bleeding and possible fetal effects ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recent literature review summarized 23 case reports on the use of systematic thrombolysis as treatment for massive PE in pregnant patients. 55 No maternal deaths occurred, and fetal deaths were reported in 2 of 23 (9%) cases. Bleeding complications were reported in 9 of 23 (39%) cases of which 5 of 23 (22%) were major bleeding.…”
Section: Treatment Of Acute Pulmonary Embolism In Pregnancymentioning
confidence: 95%